FRACTIONATION OF SILICON ISOTOPES BY MARINE DIATOMS DURING BIOGENIC SILICA FORMATION - De La Rocha C.L.; Brzezinski M.A.; DeNiro M.J. (My University, 1997)
The fractionation of silicon isotopes by three species of marine diatoms, Skeletonema costatum, Thalassiosira weissflogii, and Thalassiosira sp., grown in batch culture, is reported. Fractionation was observed for all species. The δ30Si value of the diatom silica and that of the initial silicic acid in the culture medium were used to compute a fractionation factor (α). The values of α for the three species were nearly identical, averaging 0.9989 +/- 0.0004 (s.d., n = 13), which corresponds to the production of diatom silica with a δ30Si value that is 1.1%% more negative than that of the dissolved silicon utilized for growth. The fractionation factor did not vary with temperature and the consequent change in growth rate (ANOVA, p = 0.61; tested at 12°, 15°, and 22°C with Thalassiosira sp.). The observation of fractionation of silicon isotopes by diatoms is an essential step in establishing δ30Si variations in biogenic silica as a potential oceanographic tracer.